Dorothy C. Miller, Chase Manhattan and American Banking: Investing Art? - Christine Zumello (European Journal of American Studies)
This article offers an exploration of the imbrications of “business and art” in the United States in the second half the 20th century. It brings to the fore the essential, and understudied, role of a major intermediary: Dorothy Canning Miller. As a curator working for the Museum of Modern Art (MoMA), she played a growing, and pivotal role in the Art Committee at Chase Manhattan Bank. Her work at both the MoMA and on the Art Committee of Chase helps us grasp several layers of art intermediation. The Committee set up in 1959 is a de facto intermediary as a structure. And its composition denotes the paramount importance of such new defining artistic, architectural and business trends at the end of the 1950s as corporate modernism, abstraction and new conceptual approaches of business and bank management, as well as the physical space of bank offices and the space devoted to art in almost each single one of those offices. Within that Art Committee the influence of Dorothy Miller, rises to attain great prominence over the more than 20 years when she advised Chase in art purchases as a member of that committee. She was also involved, first hand, in the perusal of the works and their downright installation as intermediaries—in business and in the physical space of the bank itself, more especially in the iconic buildings and locations which were opened at the end of the 1950s and the turn of the 1960s in the Upper East Side (410 Park Avenue) and downtown in the Financial District of Manhattan (One Chase Manhattan Plaza).